Prolonged Elevations of Factor VIII and von Willebrand Factor Antigen After Multisystem Inflammatory Syndrome in Children. Issue 4 (24th May 2023) - Boucher, Alexander A.; Knutson, Stacie; Young, Luke; Evans, Michael D.; Braunlin, Elizabeth; Zantek, Nicole D.; Sharon, Bazak; Binstadt, Bryce A.; Ryan, Meghan; Greene, Ryan; Mahmud, Shawn; Marmet, Jordan; et al.
Abstract : Multisystem Inflammatory Syndrome in Children (MIS-C) is a late systemic inflammatory response to a recent mild or asymptomatic coronavirus disease of 2019 infection. The pathophysiology is incompletely understood but it often features significant coagulopathy along with cardiac and endothelial dysfunction. Endothelial inflammation has been primarily described in acute coronavirus disease of 2019 infection, with less characterization in MIS-C. Here we describe novel findings of nearly universal severe and prolonged factor VIII (FVIII) and von Willebrand factor antigen elevations in an institutional cohort of patients with MIS-C ages younger than or 21 years old (N=31). All patients had elevated acute phase reactants and D-dimer at presentation and met published criteria for MIS-C. FVIII was high at presentation in 97% of patients but continued to rise during the ensuing weeks of treatment to a mean 429%, peaking on median day 17 of illness as an outpatient. FVIII levels were >600% in multiple patients. von Willebrand factor antigen was measured less frequently but showed similar trends. These escalations occurred amidst resolving cardiac dysfunction and acute phase reactant normalization and despite patients receiving multimodal anti-inflammatory treatments and aspirin and enoxaparin thromboprophylaxis. No thrombotic events occurred. Endothelial dysfunction represented by very elevated FVIII levels may persist longer than other acute phase reactants may reflect.